PERAN AKUNTANSI DALAM ERA CYBERSPACE - Sofyan S. Harahap (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2002)
The advance in almost all aspects of technologies has changed almost all of our daily life and put our world in a different situation compared to that of situation 20 years ago. Economy, management, accounting, and decision science have also affected by such changes. The effect is enormous. If we do not have any effort to respond this change it will affect the future of our discipline and community. The paper discusses this phe-nomena and how those changes affect accounting, and the response of accounting profession, education program on those changes.Keywords: cyberspace, accounting, information, decision making